How Individual and Contextual Factors Affects Antisocial and Delinquent Behaviors: A Comparison between Young Offenders, Adolescents at Risk of Social Exclusion, and a Community Sample - Duran-Bonavila, Silvia; Vigil-Colet, Andreu; Cosi, Sandra; Morales-Vives, Fabia (Frontiers in Psychology, 2017)
The problems associated with violence during adolescence have been on the rise in recent decades. Many studies have focused only on environmental causes or individual causes of violence, although a combination of both variables would seem to be the best option for prediction. The current study aims to assess the relevance of individual characteristics (personality traits, intelligence, and historical and clinical factors linked to the risk of violence), contextual risk factors and protective factors in explaining antisocial and delinquent behaviors in adolescence by comparing three different samples: a community sample, a sample at risk of social exclusion and a sample of juvenile offenders. The results show that the samples at risk of social exclusion and the sample of juvenile offenders have a very similar profile in terms of personality traits and intelligence, although they differ from the community sample. However, these two samples do differ in such contextual variables as peer delinquency, poor parental management, community disorganization or early caregiver disruption.